2011
DOI: 10.1002/nbm.1559
|View full text |Cite
|
Sign up to set email alerts
|

A method for rapid in vivo measurement of blood T1

Abstract: We present a technique to measure the longitudinal relaxation time constant of venous blood (T(1b) ) in vivo in a few seconds. The MRI sequence consists of a thick-slab adiabatic inversion, followed by a series of slice-selective excitations and single-shot echo planar imaging readouts. The time intervals between excitations were chosen so that blood in macroscopic vessels is fully refreshed between excitations, making the blood signal follow an unperturbed inversion recovery curve. Static tissue, which experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(130 citation statements)
references
References 16 publications
6
120
3
1
Order By: Relevance
“…The T1 relaxation of blood (T1 b ) can influence the accuracy of ASL perfusion measurements. 26,37 Previous studies have shown higher mean T1 b values (6%-9%) in women than in men, and the lower blood hematocrit level in women than in men may explain this observed sex difference in mean T1 b . [38][39][40] In a previous study, Piechnik et al 40 found significantly higher mean T1 b values in women than in men (1577 vs 1491 ms, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…The T1 relaxation of blood (T1 b ) can influence the accuracy of ASL perfusion measurements. 26,37 Previous studies have shown higher mean T1 b values (6%-9%) in women than in men, and the lower blood hematocrit level in women than in men may explain this observed sex difference in mean T1 b . [38][39][40] In a previous study, Piechnik et al 40 found significantly higher mean T1 b values in women than in men (1577 vs 1491 ms, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…65 Blood T1 variations have a greater effect on perfusion than tissue T1 variations. 69 Varela et al 70 established a linear correlation between the inverse of blood T1 and hematocrit in 12 neonates. This may offer the possibility of blood T1 estimations from recent hematocrit measurements.…”
Section: Brain Perfusion Measurements By Using Mr Imagingmentioning
confidence: 99%
“…For the blood T 1 maps, a T 1 inversion recovery sequence was used that consisted of a presaturation pulse followed by a single adiabatic inversion pulse and single-shot echo planar imaging as a readout. 17 Scan parameters were TR/TE/ΔTI/TI1: 15 seconds/20 ms/150 ms/20 ms, 60 phases, scan matrix 128 × 128, field of view 240 × 240, flip angle 95º, slice thickness 3mm, and sense 2.5. The imaging plane of the blood T 1 sequence was positioned perpendicular to the superior sagittal sinus based on the sagittal angiography image.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%